Late sequelae of COVID-19 and its effect on the quality of life (Journal of Fatima Jinnah Medical University, 2022)
Background: COVID pneumonitis presents with symptoms of fever, cough, fatigue, myalgia, inability to smell and shortness of breath. However, certain symptoms have been reported to be persistent in some people or novel post-recovery symptoms have developed. Due to the day today rise in the number of covid-19 cases in Pakistan, it is the need of the hour to determine the long-term consequences associated with this disease, to educate the general population and to establish the long-term management of the patients.Patients and methods: This cross-sectional study was conducted using non-probability purposive sampling, in which a total of 75 patients who had recovered from Covid-19 infection in the past 2-10 months visiting tertiary care hospitals in Lahore for follow up were recruited and filled survey forms bearing different questions regarding their disease, post-recovery symptoms and quality of life. Data collected was then analyzed by SPSS-26.Results: The most common symptoms were fatigue (66.7%), dry cough (46.7%), headache (44%) and joint pains (41.3%), followed by other general, neurological, pulmonary and psychological symptoms. The quality of life was analyzed in different domains exhibiting an average range of 60-68% which shows that covid-19 has significantly affected the quality of life of its victims.Conclusion: Various post disease recovery symptoms have been seen in the covid-19 victims and their quality of life has been deteriorated in physical, psychological, environmental and social domains; therefore, we need a multi-disciplinary team comprising of physicians, nurses, psychologists, social and occupational health workers who should work in liaison to tackle with these issues.
Keywords: COVID-19; late sequelae; SARS-CoV-2; quality of life